SYMBOLIC MEANINGS OF KEMBAR MAYANG IN JAVANESE WEDDING CEREMONY AT DESA MEDAN SINEMBAH KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Indra Purnawan Panjaitan; M Manugeren (JOURNAL OF LANGUAGE, 2019)
This study is aimed at analyzing the symbolic meanings of Kembar Mayang conducted at Desa Medan Sinembah Kecamatan Tanjung Morawa Kabupaten Deli Serdang predominantly by Javanese ethnic. Kembar Mayang in this study is concerned with the Javanese wedding ceremony. Descriptive qualitative method is applied in the study describing social phenomena occurring naturally aiming to help us to understand the world in which we live and why things are in the way they are. The main theory to support the study is the theory of Semiotic. The results show there are five forms of symbolic meanings in Kembar Mayang: Manuk-Manukan as symbol of Loyalty; Uler-Uleran of Struggle; Walang-Walangan of Persistence; Pecut-Pecutan of Optimism and Keris-Kerisan of Wisdom. The five forms of rites are compulsory in the wedding ceremony with the main objective to achieve a happy, harmonious and peaceful life for the bride and the bridegroom and this is in line with the general concept of marriage.